Perceived importance on Malaysian halal and authentic heritage food (HAHFo): international Muslim tourists' purchase intention behaviour - Omar, Siti Nazirah; Omar, Siti Radhiah; Abdul Karim, Muhammad Shahrim (International Organization Center of Academic Research, 2014)
As a Muslim country, Malaysia had received tremendous numbers of international Muslim visitors from all around the world and it was increasing from year to year. The major reason this country became an attractive destination for Muslim travelers is: Malaysia offers of a great, wide range incredible, splendid cuisine from three major ethnicities which are Malay, Chinese and Indian that symbolized the food culture. However, research has been revealed that Malaysian Heritage Food (MHF) is having a serious problem among Muslim tourists whereby they have the limitation to experience diversity of food culture due to non-halal issue and lack of confidence to purchase. In fact, the availability of halal kitchen and restaurants that served authentic heritage food from multiple ethnicities especially Indian and Chinese cuisines is also a typical concern. Thus, this paper aimed to address the gap by examining the importance of Halal and Authentic Heritage Food (HAHFo) and food culture experiences among Muslim tourists in establishing ethnic restaurants, kitchens, and food service providers with HAHFo concept. Data were collected by distributing questionnaires to Muslim tourists preferably who were visited in Kuala Lumpur. Findings discovered a highly significant importance for multi-ethnicity food providers to practice halal procedures in convincing Muslim tourists to choose variety of cuisines offered. Multiple regression analysis was used in this study to assess the relative importance of HAHFo dimensions towards protecting the authenticity of MHF. Finally, the results outline some possible practical recommendations for heritage food service provider who might pursue with marketing strategies towards serving HAHFo among Muslim international tourists and promoting Malaysia as a hub of diversity halal food culture for tourists’ destination.